1976
DOI: 10.1136/gut.17.8.576
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum alpha-fetoprotein in fulminant hepatic failure including patients treated by charcoal haemoperfusion.

Abstract: SUMMARY Serum alpha-fetoprotein (AFP) levels have been measured sequentially by a radioimmunoassay method in 64 patients with fulminant hepatic failure. In 15 of the 64 patients (23 %) AFP levels were raised but in only two did they exceed 500 ng/ml. Of the 23 survivors 11 (48 %) had raised AFP levels compared with four of the 41 (9-8 %) fatal cases (p < 0 005). This rise in AFP levels was found early after the development of grade IV coma and constitutes an encouraging prognostic sign at a time when the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…Previously, AFP in acetaminophen poisoning had only been studied using the radio immunoassay. 15,19 However, more recent studies in non-acetaminophen-induced FHF using the EIA have produced results very similar to those in the present study. 24,25 AFP EIA may be performed as a routine analysis at a very limited cost (approximately $9 at our laboratory), which makes it practical as a prognostic marker for clinical use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previously, AFP in acetaminophen poisoning had only been studied using the radio immunoassay. 15,19 However, more recent studies in non-acetaminophen-induced FHF using the EIA have produced results very similar to those in the present study. 24,25 AFP EIA may be performed as a routine analysis at a very limited cost (approximately $9 at our laboratory), which makes it practical as a prognostic marker for clinical use.…”
Section: Discussionsupporting
confidence: 89%
“…12 In FHF, AFP has been studied predominantly in patients with non-acetaminophen-induced liver failure, and the majority of studies find that an elevation of AFP is associated with a favorable prognosis. 15,[17][18][19][20][21][22][23][24][25] Only a few, older studies have included patients with acetaminophen poisoning. 15,19 Thus, the prognostic value of AFP in acetaminophen-induced hepatotoxicity is widely undetermined.…”
mentioning
confidence: 99%
“…90 42 Not reported. [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] AH, acute hepatitis; ALF, acute liver failure; FHF, fulminant hepatic failure; HALF, hyperacute liver failure; HE, hepatic encephalopathy; HPT, hepaplastin test; INR, international normalised ratio; PT, prothrombin time; PTA, prothrombin time activity; SALF, subacute liver failure; SubFHF, subacute fulminant hepatic failure.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of serum alfa-fetoprotein (AFP) in patients with FHF was suggested nearly 3 decades ago, 12 where it was shown that in a very small series of patients, survivors had a higher serum AFP (Ͼ50 ng/mL) and a rising serum AFP and this could help identify patients with a poor prognosis. A subsequent study 20 confirmed these observations but suggested that the higher levels, which reflected hepatic regenerative activity, may reflect merely a temporal effect.…”
mentioning
confidence: 99%
“…Other markers are listed in Table 1. [11][12][13][14][15][16][17][18][19] Some may be of little importance and merely reflect that the sicker the patient, the worse the outcome and the more abnormal the measurement, so it is not surprising there would be a correlation with outcome. Some markers, such as the degree of liver cell necrosis and liver size, may well have the necessary statistical power to show a significant correlation with survival, but they are either impractical to measure or subject to significant observer variation.…”
mentioning
confidence: 99%